In Vitro Expansion of Bone Marrow Derived Mesenchymal Stem Cells Alters DNA Double Strand Break Repair of Etoposide Induced DNA Damage - Ian Hare; Marieta Gencheva; Rebecca Evans; James Fortney; Debbie Piktel; Jeffrey A. Vos; David Howell; Laura F. Gibson (Stem Cells International)
Mesenchymal stem cells (MSCs) are of interest for use in diverse cellular therapies. Ex vivo expansion of MSCs intended for transplantation must result in generation of cells that maintain fidelity of critical functions. Previous investigations have identified genetic and phenotypic alterations of MSCs with in vitro passage, but little is known regarding how culturing influences the ability of MSCs to repair double strand DNA breaks (DSBs), the most severe of DNA lesions. To investigate the response to DSB stress with passage in vitro, primary human MSCs were exposed to etoposide (VP16) at various passages with subsequent evaluation of cellular damage responses and DNA repair. Passage number did not affect susceptibility to VP16 or the incidence and repair kinetics of DSBs. Nonhomologous end joining (NHEJ) transcripts showed little alteration with VP16 exposure or passage; however, homologous recombination (HR) transcripts were reduced following VP16 exposure with this decrease amplified as MSCs were passaged in vitro. Functional evaluations of NHEJ and HR showed that MSCs were unable to activate NHEJ repair following VP16 stress in cells after successive passage. These results indicate that ex vivo expansion of MSCs alters their ability to perform DSB repair, a necessary function for cells intended for transplantation.